Aggressive intravenous hydration protocol of Lactated Ringer’s solution benefits patients with mild acute pancreatitis: A meta-analysis of 5 randomized controlled trials - Wu, Fei; She, Dong; Ao, Qin; Zhang, Shan; Li, Jin (Frontiers in Medicine, 2022)
Objective The aim of this meta-analysis was to determine the role of an aggressive intravenous hydration protocol of Lactated Ringer’s solution in patients with mild acute pancreatitis (MAP). Methods A systematic search was conducted in PubMed, EMBASE, Cochrane Library, and China National Knowledge Infrastructure (CNKI) to identify randomized controlled trials (RCTs) published before August 19, 2022. The clinical outcomes were evaluated using the standard mean difference (SMD), mean difference (MD), risk ratio (RR), and 95% confidence interval (CI). The primary outcome was clinical improvement, while the secondary outcomes were the development of systemic inflammatory response syndrome (SIRS) and multiple organ dysfunction syndrome (MODS), relief of epigastric abdominal pain, and length of hospital stay (LoH). Statistical analysis was performed with RevMan 5.4. Grades of Recommendation, Assessment, Development, and Evaluation (GRADE) Working Group system was used to determine the quality of evidences. Results There were five RCTs with 370 MAP patients included, and the overall methodological quality was moderate. Aggressive hydration protocol was comparable to standard hydration protocol in terms of clinical improvement (RR = 1.33, 95%CI = 0.95–1.87, P = 0.10; very low evidence). Fewer events of SIRS (RR = 0.48, 95%CI = 0.31–0.72, P < 0.001; low evidence) and MODS (RR = 0.34, 95%CI = 0.13–0.91, P = 0.03; moderate evidence) were reported in patients receiving aggressive hydration protocol. Meanwhile, aggressive hydration protocol also significantly relieved epigastric abdominal pain (SMD = −0.53, 95%CI = −0.81 to −0.25, P < 0.001; low evidence) and shorten the LoH (MD = −2.36, 95%CI = −3.17 to −1.55, P < 0.001; low evidence) compared with standard hydration protocol. Conclusion For patients with MAP, aggressive hydration protocol may be more effective than standard hydration protocol at lowering SIRS and MODS rates, relieving epigastric abdominal pain, and shortening the LoH. Due to the small number of studies that are eligible and poor methodological quality of eligible studies, further studies are required to validate our findings.